Pneumothorax and Pneumomediastinum in Pregnancy: A Case Report - S. Sathiyathasan; K. Jeyanthan; G. Furtado; R. Hamid (Hindawi Limited, 2009)
Case Report. A 37 years old patient at 40 weeks gestation presented with acute severe hypoxia with a seizure followed by fetal bradycardia. Caesarean section was performed under GA and she was intubated and ventilated. History revealed longstanding right pleural endometriosis with multiple pneumothoraces and hydrothoraces. A CT chest showed extensive bilateral pnenumothoraces. Her clinical condition improved with a left-sided chest drain. Discussion. Severe hypoxia and seizures in a patient with previous history of pnenumothorax are highly suggestive of tension pneumothorax. Radiological investigations are vital for diagnosis. The traditional treatment approach to recurrent pneumothorax has been thorocotomy with bleb or bulla resection and pleurodeisis. The advantages of thorocoscopic surgical treatment over thorocotomy are decreased time of exposure to anaesthetic drugs, rapid lung expansion, decreased post operative pain, and a potentially shorter post operative recovery. In any future pregnancy due to the high risk of recurrence of pneumothorax Contemporary obstetric management should determine the method of delivery and continuous lumbar/epidural anesthesia should be used if at all feasible. Preconceptual counseling about this risk is vital, and women must be advised about potential serious adverse outcomes.